Zero by 2030 and OneHealth: The multidisciplinary challenges of rabies control and elimination - Bonilla-Aldana, D. Katterine (2022)
“Rabies, caused by a negative strand RNA-virus belonging to the genus Lyssavirus (family Rhabdoviridae of the order Mononegavirales), remains of global concern [1]. This vaccine-preventable viral zoonotic disease is present in more than 150 countries and territories [2]. Ac- cording to the World Health Organization (WHO), rabies is estimated to cause ~59,000 human deaths annually, with 95% of cases occurring in Africa and Asia [3,4]. However, rabies still occurs in other regions, such as Latin America and the Caribbean [5–8], Central Asia and the Middle East [9,10]. Whilst a number of animals can host the rabies virus, dogs are the main source of human rabies deaths, contributing up to 99% of all rabies transmissions to humans. Dog-mediated rabies has been eliminated from Western Europe, Canada, the United States of America (USA), Japan and some Latin American countries [11]. Nevertheless, the risk of reintroduction and disease among travellers to risk areas is a matter of concern [12–15]. As occurred with many other communicable and non-communicable diseases, the 2020–2022 COVID-19 pandemic negatively impacted the efforts of control and reemergence of rabies in certain countries [7,16,17]. Post-pandemic challenges to enhance con- trol and prevention are multiple and need urgent actions to achieve the goal in eight years by 2030 [16].“